2022
DOI: 10.3389/fimmu.2022.1020159
|View full text |Cite
|
Sign up to set email alerts
|

Immunological study of COVID-19 vaccine candidate based on recombinant spike trimer protein from different SARS-CoV-2 variants of concern

Abstract: The emergency of new SARS-CoV-2 variants that feature increased immune escape marks an urgent demand for better vaccines that will provide broader immunogenicity. Here, we evaluated the immunogenic capacity of vaccine candidates based on the recombinant trimeric spike protein (S) of different SARS-CoV-2 variants of concern (VOC), including the ancestral Wuhan, Beta and Delta viruses. In particular, we assessed formulations containing either single or combined S protein variants. Our study shows that the formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 71 publications
4
14
0
Order By: Relevance
“…During the pre-vaccination period, the coronavirus disease 2019 (COVID-19) pandemic substantially burdened the world medically and socioeconomically, with the major determinant of patients’ survival relying solely on supportive measures ( 1 ). By inducing certain inflammatory cascades ( 2 ), COVID-19 vaccination induces the production of pathogen-specific neutralizing antibodies ( 3 ), which plays a significant role in decelerating the disease spreading and reducing the cases of COVID-19-related organ failure, hospitalization and mortality, allowing a gradual resume of pre-pandemic lifestyle in many parts of the world ( 4 , 5 ). Nonetheless, emerging COVID-19 variants and the spike in disease incidence associated with waning immunity emphasize the importance of maintaining high-level immunity to prevent the COVID-19 pandemic from rehappening ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the pre-vaccination period, the coronavirus disease 2019 (COVID-19) pandemic substantially burdened the world medically and socioeconomically, with the major determinant of patients’ survival relying solely on supportive measures ( 1 ). By inducing certain inflammatory cascades ( 2 ), COVID-19 vaccination induces the production of pathogen-specific neutralizing antibodies ( 3 ), which plays a significant role in decelerating the disease spreading and reducing the cases of COVID-19-related organ failure, hospitalization and mortality, allowing a gradual resume of pre-pandemic lifestyle in many parts of the world ( 4 , 5 ). Nonetheless, emerging COVID-19 variants and the spike in disease incidence associated with waning immunity emphasize the importance of maintaining high-level immunity to prevent the COVID-19 pandemic from rehappening ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated the immunogenicity capacity of the SW-Vac 2μg vaccine candidate in a mouse model used for primary immunization schemes as well as boosters (20). This vaccine contains the soluble glycosylated trimeric prefusion stabilized spike protein derived from the ancestral virus.…”
Section: Resultsmentioning
confidence: 99%
“…Two commercial vaccine platforms, mRNA1273 (mRNA-based vaccine) and AZD1222 (non-replicative vector-based vaccine AZD1222/ChadOx1), were used for a two-dose primary series. As a 12 heterologous booster, we employed our vaccine candidate based on the glycosylated trimeric spike protein formulated with Alhydrogel (20). In a previous report, we demonstrated that the formulation containing the protein from the ancestral SARS-CoV-2 variant at a dose of 2 μg (SW-Vac 2μg), as well as the formulation containing the same dose of the Delta variant (SD-Vac 2μg), are immunogenic in both homologous and heterologous schemes, primarily when used as a heterologous booster in combination with the Gam-COVID-Vac-rAd26/rAd5 vaccine (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the COVID-19 pandemic, an important focus of our research has been the production of recombinant SARS-CoV-2 spike proteins in CHO cells. These proteins, specifically soluble, trimeric, prefusion-stabilized spike ectodomain constructs (Stuible et al, 2021), have been investigated as candidate vaccine antigens and also as reagents for serosurveillance studies (Akache et al, 2021(Akache et al, , 2022Chisanga et al, 2022;Colwill et al, 2022;Rudi et al, 2022;Stark et al, 2022;Stocks et al, 2021). With the frequent emergence of new variants, we have had the opportunity to generate dozens of spike-expressing CHO pools over the last 2 years, which has allowed us to appreciate better the performance and robustness of this expression platform.…”
Section: Introductionmentioning
confidence: 99%